국내 민간투자사업 리스크 재분담의 재무적 영향성 분석 - 민간투자자 간 지분거래 및 약정거래를 중심으로 - 주창환; 권병기; 이현수; 박문서; Chu, Chang Hwan; Kwon, Byungki; Lee, Hyun-soo; Park, Moonseo (한국건설관리학회 논문집, 19(2), 2018)
In recent times, private sector allocates the risk between private sector investors in terms of equity transaction and agreement transaction. The additional risk-allocation have made the cash flows of private sector investors fluctuated and some of the PPP projects delayed. Therefore, analyzing the impact of the risk reallocation between private sector investors on their cash flows is critical for encouraging the private sector participants. In this study, a model to evaluate the financial viability of PPP project is developed based on the discounted cash flow analysis. The model can analyze the variability by equity and agreement transaction by identifying key variables of equity transaction, influence factors of agreement transaction, and relationship between the transactions and investor's profitability. It is expected that the private sector can determine the investment decision for PPP projects when the risk reallocation is occurred. 민간투자자 사이에서의 리스크 재분담은 민간투자자의 현금흐름에 추가적인 변동성을 야기하며, 민간부문의 투자결정에 있어 제약요인이 되고 있다. 하지만 기존의 재정건전성 평가모델은 지분거래와 약정거래가 충분히 반영되지 않아, 민간투자자 간 리스크 재분담에 따른 현금흐름의 변동성을 분석하기에 한계가 있다. 본 연구는 민간투자자 사이에서 이루어지는 지분거래와 약정거래를 분석하고, 이를 반영한 민간투자자의 재무적 평가 모델을 개발하였다. 또한, 개발된 모델의 실증적 분석을 통해 지분거래의 주요변수와 약정거래의 영향요인을 도출하였으며, 민간투자자 간 리스크 재분담과 민간투자자의 수익률 간의 관계를 증명하였다. 본 연구는 리스크 재분담에 대한 민간투자자의 의사결정에 기여할 것이며, 더 나아가 민간투자사업의 협약지연의 문제를 관리하는데 도움이 될 것이다.